6.6(x-1)=-0.4x+35.4

Simple and best practice solution for 6.6(x-1)=-0.4x+35.4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6.6(x-1)=-0.4x+35.4 equation:


Simplifying
6.6(x + -1) = -0.4x + 35.4

Reorder the terms:
6.6(-1 + x) = -0.4x + 35.4
(-1 * 6.6 + x * 6.6) = -0.4x + 35.4
(-6.6 + 6.6x) = -0.4x + 35.4

Reorder the terms:
-6.6 + 6.6x = 35.4 + -0.4x

Solving
-6.6 + 6.6x = 35.4 + -0.4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.4x' to each side of the equation.
-6.6 + 6.6x + 0.4x = 35.4 + -0.4x + 0.4x

Combine like terms: 6.6x + 0.4x = 7x
-6.6 + 7x = 35.4 + -0.4x + 0.4x

Combine like terms: -0.4x + 0.4x = 0.0
-6.6 + 7x = 35.4 + 0.0
-6.6 + 7x = 35.4

Add '6.6' to each side of the equation.
-6.6 + 6.6 + 7x = 35.4 + 6.6

Combine like terms: -6.6 + 6.6 = 0.0
0.0 + 7x = 35.4 + 6.6
7x = 35.4 + 6.6

Combine like terms: 35.4 + 6.6 = 42
7x = 42

Divide each side by '7'.
x = 6

Simplifying
x = 6

See similar equations:

| 2+r=7 | | 73-4=2 | | 6.67x+100=44.4889+10x | | -2y+7=77 | | 1=1/4x | | 5w-9w=56 | | 5+1*2= | | 27*3.14=3.14n | | -4t+9=105 | | 1+1*5= | | 1+1*2= | | -7=-y+1 | | 0=4x^3+24x^2+36x | | 2x+4=5(x+1)-3(x+3) | | x+50=x+85 | | -z-6=6 | | -0.1(-27.6-2x)=0.5x | | 1/x=.12345678901234567890 | | 9x-25=180 | | -a+7=53 | | b=3+b | | x^2+2x=x+4 | | -5(0.4+0.2y)+y=-2 | | -9(a+12)=45 | | -(6x^2)-500x-20000=0 | | 6x-3.5=0 | | 500/250*1 | | 5n^2-28=-13n | | 250/500*1 | | 12y-40=4Y | | a+12*3=6 | | 3=1/3x-3 |

Equations solver categories